Comparison of the Changes in Seed Germination Vigour with Prolonged Postharvest Storage for Hordeum vulgare Varieties, Hope and Sierra Malting Barley Varieties, in Zimbabwe - Milford Mwazha; Desmond T Mugadza; Shepherd Manhokwe; Michael Njini; Talknice Z Jombo (Journal of Food Quality)
To ensure production of quality malt that conforms to brewing requirements, the barley used should have minimal postharvest dormancy and be able to germinate rapidly and uniformly. The objective of the study was to compare the changes in seed germination, vigour trends, and storage stability of two-row Zimbabwean commercially grown malting barley varieties (Hope and Sierra), as the postharvest storage time increased. The two varieties were stored for 12 months, and at monthly intervals, germination index, capacity, and energy were determined. In addition, other quality parameters (protein content, screening, moisture content, water sensitivity, and insect damage index) were also assessed. Hope’s germination index improved with an increase in storage time from 8.67 at the beginning of the study to 9.18 at the end of the study, while that for Sierra diminished with storage from 9.35 to 6.71. Generally, water sensitivity improved with postharvest storage for both varieties. However, the germination energy for Hope diminished with increased postharvest storage compared to Sierra. Hope variety is the more suitable variety for extended postharvest storage than Sierra. However, Sierra variety is more suitable for early malting postharvest storage.